2021
DOI: 10.1093/advances/nmaa121
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Assessment and Preparation for Adult Bariatric Surgery Candidates: Clinical Practice

Abstract: Bariatric surgery (BS) has proven to be highly efficacious in the treatment of obesity and its comorbidities. However, careful patient selection is critical for its success. Thus, patients should undergo medical, behavioral, and nutritional assessment by a multidisciplinary team. From the nutritional point of view, BS candidates should undergo nutritional assessment, preparation, and education by a registered dietitian in the preoperative period. Currently, detailed specified and comprehensive information on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 145 publications
0
25
0
Order By: Relevance
“…Regardless of the type of planned surgery, all BS candidates should be submitted to a comprehensive nutritional, medical and health-related behavior assessment prior to surgery, followed by suitable counseling and intervention. Patients planning to undergo BS must be also provided with appropriate knowledge about the surgical treatment for weight loss [31,32]. Preoperative screening of baseline nutritional deficiencies should be performed (Table I) [33] and adequate nutritional supplementation, based on micronutrient laboratory tests results, should be recommended [16].…”
Section: Preoperative Evaluation Of Bs Candidatesmentioning
confidence: 99%
“…Regardless of the type of planned surgery, all BS candidates should be submitted to a comprehensive nutritional, medical and health-related behavior assessment prior to surgery, followed by suitable counseling and intervention. Patients planning to undergo BS must be also provided with appropriate knowledge about the surgical treatment for weight loss [31,32]. Preoperative screening of baseline nutritional deficiencies should be performed (Table I) [33] and adequate nutritional supplementation, based on micronutrient laboratory tests results, should be recommended [16].…”
Section: Preoperative Evaluation Of Bs Candidatesmentioning
confidence: 99%
“…Even then, nutritional counselling is safe, requires minimal resources, helps to create a rapport with the bariatric team and prepares the patient for necessary lifestyle modifications required around and after the surgery. It is an important adjunct to comprehensive bariatric care and is recommended by most guidelines[ 33 , 136 , 200 ].…”
Section: Nutritional Assessment and Optimizationmentioning
confidence: 99%
“…Estimation of serum vitamin B12 and folate levels are recommended before surgery[ 33 , 223 ]. Low vitamin B12 should be treated by parenteral administration in megaloblastic anemia, neuropathy, or in presence of other deficiency symptoms[ 33 , 200 , 223 - 225 ]. A systemic review by Smelt et al [ 226 ] suggested that daily oral administration of 350 μg of vitamin B12 corrects low levels in most cases.…”
Section: Nutritional Assessment and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Suboptimal postoperative weight results are often attributed to a return to maladaptive lifestyle behaviors, poor adherence to the postoperative diet, inadequate follow-up support with the dietitian, or low patient knowledge, rather than surgical or metabolic reasons [ 5 , 6 , 7 ]. Therefore, pre- and postoperative nutritional intervention programs should be studied, and, if successful, be implemented into clinical practice [ 8 , 9 ].…”
mentioning
confidence: 99%